A Scoping Review of Policies Related to the Prevention and Control of Overweight and Obesity in Africa - Theodosia Adom (MDPI AG, 2021)
To address the issue of obesity, the World Health Organization (WHO) recommends a set of comprehensive programmes aimed at changing the obesogenic environments to provide opportunities for healthy food options and increased physical activity in the school, home, and at the population level. The objectives of this study were to examine the nature and range of policies related to overweight and obesity prevention in Africa, and to assess how they align with international guidelines. An existing methodological framework was adapted for this scoping review. A search of publicly available national documents on overweight/obesity, general health, and non-communicable diseases (NCDs) was undertaken from relevant websites, including WHO, ministries, and Google Scholar. Additional requests were sent to key contacts at relevant ministries about existing policy documents. The documents were reviewed, and the policies were categorised, using the Analysis Grid for Environments Linked to Obesity (ANGELO) framework. The framework categorises the environmental drivers of obesity into four domains (physical, economic, legislative, and socio-cultural) and two scales: macro (national, regional, sectors, food industries, media, etc.) and micro (household, institutional, and community). This review included documents from 41 African countries. The policy initiatives to prevent overweight/obesity target the school, family and community settings, and macro environments, and broadly align with global recommendations. The NCD documents were in the majority, with only two on obesity. The majority of the documents detailed strategies and key interventions on unhealthy diets and physical inactivity. The physical, legislative, and sociocultural domains were largely featured, with less emphasis on the economic domain. Additionally, nutrition- and diet-related policies were in the majority. Overlaps and interactions of policies were observed in the application of the ANGELO framework. This study has provided information on national policies and programmes in Africa and can be useful as a first point of call for policymakers. The overlapping and interaction in the initiatives demonstrate the importance of multi-sectoral partnerships in providing supportive environments for healthy behaviours.